Systematic review of exercise for Charcot‐Marie‐Tooth disease. Issue 4 (December 2015) - Sman, Amy D.; Hackett, Daniel; Fiatarone Singh, Maria; Fornusek, Ché; Menezes, Manoj P.; Burns, Joshua
Abstract: Charcot‐Marie‐Tooth disease (CMT) is a slowly progressive hereditary degenerative disease and one of the most common neuromuscular disorders. Exercise may be beneficial to maintain strength and function for people with CMT, however, no comprehensive evaluation of the benefits and risks of exercise have been conducted. A systematic review was completed searching numerous electronic databases from earliest records to February 2015. Studies of any design including participants of any age with confirmed diagnosis of CMT that investigated the effects of exercise were eligible for inclusion. Of 13, 301 articles identified following removal of duplicates, 11 articles including 9 unique studies met the criteria. Methodological quality of studies was moderate, sample sizes were small, and interventions and outcome measures used varied widely. Although the majority of the studies identified changes in one or more outcome measurements across exercise modalities, the majority were non‐significant, possibly due to Type II errors. Significant effects described included improvements in strength, functional activities, and physiological adaptations following exercise. Despite many studies showing changes in strength and function following exercise, findings of this review should be met with caution due to the few studies available and moderate quality of evidence. Well‐powered studies, harmonisation of outcome measures, and clearly described interventions across studies would improve the quality and comparability of the evidence base. The optimal exercise modality and intensity for people with CMT as well as the long‐term safety of exercise remain unclear.